Phenolic Compounds and Organic Acid Composition of Syringa vulgaris L. Flowers and Infusions - Monika Gąsecka; Agnieszka Krzymińska-Bródka; Zuzanna Magdziak; Piotr Czuchaj; Joanna Bykowska (Molecules, 2023)
The study aimed to determine the content of phenolic compounds (phenolic acids and flavonoids) and organic acids in dried flowers and water infusions of non-oxidised and oxidised flowers from four lilac cultivars. The diversity in the total phenolic and flavonoid content was in the flowers (18.35–67.14 and 2.03–2.65 mg g−1 DW, respectively) and infusions (14.72–47.78 and 0.20–1.84 mg per 100 mL infusion, respectively) depending the flower colour and form (oxidised and non-oxidised). Phenolic compounds and organic acids were susceptible to oxidation. Compared to infusions, flowers had more phenolic compounds and organic acids. The highest content of most phenolic compounds was confirmed for non-oxidised purple flowers (up to 7825.9 µg g−1 DW for chlorogenic acid) while in infusions for non-oxidised white flowers (up to 667.1 µg per 100 mL infusions for vanillic acid). The phenolic profile of the infusions was less diverse than that of flowers. The scavenging ability ranged from 52 to 87%. The highest organic acid content in flowers was for oxidised blue and purple flowers (2528.1 and 2479.0 µg g−1 DW, respectively) while in infusions the highest organic acid content was for oxidised purple flowers (550.1 µg per 100 mL infusions).